Contemporaneous religious return (Psicologia USP, 2008)
The present work intends to discuss the new relations between the civilization and the sacred that appears in the contemporary context. Beginning by the Freudian and Lacanian formulations about this theme, our goal is to establish some references in order to understand the "return to the sacred" at the moment where the humanity faces deeper and more permanent crises each time. Such challenge will allow us to verify how the increase in the religious movements can be considered as a reaction against the fall of the references that happens nowadays.